2013
DOI: 10.1093/rheumatology/ket159
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal-associated membrane protein-2 plays an important role in the pathogenesis of primary cutaneous vasculitis

Abstract: These data support a positive relationship between anti-LAMP-2 antibody and cutaneous vasculitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…There have been few studies on biomarkers in polyarteritis nodosa. Autoantibodies against lysosomal-associated membrane protein-2 (LAMP-2) showed an association with dermatological signs of the disease, but in the end there was no significant difference when compared to values measured in healthy controls (66). LAMP-2 is a component of the lysosomal membrane.…”
Section: Medium Vessel Vasculitismentioning
confidence: 94%
See 2 more Smart Citations
“…There have been few studies on biomarkers in polyarteritis nodosa. Autoantibodies against lysosomal-associated membrane protein-2 (LAMP-2) showed an association with dermatological signs of the disease, but in the end there was no significant difference when compared to values measured in healthy controls (66). LAMP-2 is a component of the lysosomal membrane.…”
Section: Medium Vessel Vasculitismentioning
confidence: 94%
“…LAMP-2 is a component of the lysosomal membrane. It has been assumed that LAMP-2 plays a role in the pathogenesis of vasculitis (66). Mechanistically, Takeuchi et al hypothesize that anti-LAMP-2-antibodies bind to neutrophils, which then infiltrate small vessels of the skin (66).…”
Section: Medium Vessel Vasculitismentioning
confidence: 99%
See 1 more Smart Citation
“…Autoantibodies to the LAMP-2 protein were recently found to be associated with cutaneous PAN [25], but concentrations overlapped enough with those of healthy controls that this antibody is unlikely to be useful diagnostically.…”
Section: Polyarteritis Nodosa and Central Nervous System Vasculitismentioning
confidence: 99%
“…Cyclophosphamide decreases the immune system's response to various diseases, including vasculitis. We suggested that several autoantibodies such as antilysosomal‐associated membrane protein‐2 antibodies and antiphosphatidylserine–prothrombin complex antibodies could be closely related to the pathogenesis of CA in our previous studies . We encountered two patients with refractory CA associated with arthritis and mononeuritis multiplex, with elevated serum CRP.…”
mentioning
confidence: 91%